Common origin of both coronary arteries from LSV - Kumar, Avanish; Akhtar, Md Jawed; Mohan, Lalit (Asian Journal of Medical Sciences, 2014)
During routine dissection of a male cadaver aged about 60 years in dept. of Anatomy at IGIMS Patna a rare anomalous single coronary artery has been detected. In this case a single trunk is taking origin from LSV. Both the coronary arteries are arising from this trunk. Heart’s shape, size and weight are within normal range. On gross examination no other major congenital malformation and pathological changes is detected. In addition to this, further during dissection in other region of the body no other major vascular malformation is found. DOI: http://dx.doi.org/10.3126/ajms.v6i1.9583 Asian Journal of Medical Sciences Vol.6(1) 2015 117-118